Drug delivery systems based on polyethylene glycol hydrogels for enhanced bone regeneration - Sun, Shouye; Cui, Yutao; Yuan, Baoming; Dou, Minghan; Wang, Gan; Xu, Hang; Wang, Jingwei; Yin, Wen; Wu, Dankai; Peng, Chuangang (Frontiers in Bioengineering and Biotechnology, 2023)
Drug delivery systems composed of osteogenic substances and biological materials are of great significance in enhancing bone regeneration, and appropriate biological carriers are the cornerstone for their construction. Polyethylene glycol (PEG) is favored in bone tissue engineering due to its good biocompatibility and hydrophilicity. When combined with other substances, the physicochemical properties of PEG-based hydrogels fully meet the requirements of drug delivery carriers. Therefore, this paper reviews the application of PEG-based hydrogels in the treatment of bone defects. The advantages and disadvantages of PEG as a carrier are analyzed, and various modification methods of PEG hydrogels are summarized. On this basis, the application of PEG-based hydrogel drug delivery systems in promoting bone regeneration in recent years is summarized. Finally, the shortcomings and future developments of PEG-based hydrogel drug delivery systems are discussed. This review provides a theoretical basis and fabrication strategy for the application of PEG-based composite drug delivery systems in local bone defects.